2016
DOI: 10.23939/chcht10.04.507
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Cavitation Processes in Different Types of Emitters Using Sonochemical Analysis

Abstract: The application limits of optical and sonochemical methods to determine the sizes of cavitation bubbles and their derivatives have been analyzed. The effect of cavitation fields generated using an ultrasonic magnetostrictive oscillator and jet hydrodynamic emitter on the parameters of their acoustic signals has been examined. The bubbles size depending on emitter type and parameters has been determined using sonochemical analysis. The character of the dependence was estimated according to Minnaert formula. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Chadi et al 40 found that hydroxyl, iodyl radicals, and singlet oxygen play a key role in Toluidine blue degradation. Ultrasound intensifies heat and mass transfer processes, thereby enhancing the efficiency of organic pollutant degradation 39,[41][42][43][44][45] . For example, the use of the ultrasound/H 2 O 2 /KIO 4 process (the Sonoperoxate process) for the oxidative degradation of Methylene blue for 60 min increased the degree of dye degradation by 18.5 % (from 55.6 to 74.1 %), compared to the use of the H 2 O 2 /KIO 4 process 39 .…”
Section: Other Activation Methodsmentioning
confidence: 99%
“…Chadi et al 40 found that hydroxyl, iodyl radicals, and singlet oxygen play a key role in Toluidine blue degradation. Ultrasound intensifies heat and mass transfer processes, thereby enhancing the efficiency of organic pollutant degradation 39,[41][42][43][44][45] . For example, the use of the ultrasound/H 2 O 2 /KIO 4 process (the Sonoperoxate process) for the oxidative degradation of Methylene blue for 60 min increased the degree of dye degradation by 18.5 % (from 55.6 to 74.1 %), compared to the use of the H 2 O 2 /KIO 4 process 39 .…”
Section: Other Activation Methodsmentioning
confidence: 99%
“…Cavitation-reagent mineralization Probably, this can be explained by the coalescence (union) of cavitation bubbles under the action of Bjerknes forces. Bjerknes forces are electrostatic attraction forces that arise between spherical-shaped air bubbles in a liquid [19]. The time-averaged interaction force (F, N) between two spherical bubbles, which are pulsating in a liquid, by Bjerknes is [19]: 12 2 cos 4 F l…”
Section: Methods Of Processingmentioning
confidence: 99%
“…Суть передових процесів окиснення полягає у генеруванні тим чи іншим способом високореакційноздатних гідроксильних радикалівокисників органічних сполук різних класів, зокрема ароматичних сполук та їх похідних [14][15][16][17][18][19][20][21][22][23]. Барвники, з певними наближеннями, можна роз-глядати як похідні ароматичних сполук, оскільки вони містять бензенове кільце.…”
Section: вступunclassified